2017
DOI: 10.3390/rs9060629
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Convolutional Neural Network Land-Cover Classification of Multi-Seasonal Hyperspectral Imagery in the San Francisco Bay Area, California

Abstract: Abstract:In this study, a 1-D Convolutional Neural Network (CNN) architecture was developed, trained and utilized to classify single (summer) and three seasons (spring, summer, fall) of hyperspectral imagery over the San Francisco Bay Area, California for the year 2015. For comparison, the Random Forests (RF) and Support Vector Machine (SVM) classifiers were trained and tested with the same data. In order to support space-based hyperspectral applications, all analyses were performed with simulated Hyperspectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 28 publications
1
73
0
Order By: Relevance
“…The classification of the land cover was performed using a CNN [14,22,[31][32][33][34][35]. CNNs simulate the working of a human brain using a multilayer structure [26].…”
Section: Methodsmentioning
confidence: 99%
“…The classification of the land cover was performed using a CNN [14,22,[31][32][33][34][35]. CNNs simulate the working of a human brain using a multilayer structure [26].…”
Section: Methodsmentioning
confidence: 99%
“…The second new feature type explored uses a 2-D matrix approach. Different to the 1-D vector approach [32], the 2-D matrices are aligned with spectral bands (x axis) and time (y axis) as shown in Figure 1b. The pixel value of the first spectral band at (m, n) for the t th period is designated as pm,n,(t-1)×N+1.…”
Section: -D Feature Extractionmentioning
confidence: 99%
“…CNNs have also integrated with other algorithms, such as multilayer perceptrons [30] and support vector machines [31]. Many studies have reported that CNNs have contributed to an accuracy improvement of land cover classification, with the overall accuracy ranging from 81% to 93%, depending on the sensor type, spatial resolution of input images, and target classes [18,19,21,27,[29][30][31][32][33].Feature engineering is defined as the process of transforming raw data into features for better representation of the given problem, which can result in an improvement of the model accuracy on unseen data [34]. Good features are a contributing factor in model performance since machine learning algorithms are problem specific and dependent on their domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, W. Hu et al [13] trained a simple one-dimensional (1D) five-layer CNN that directly classifies hyperspectral images in spectral domain. D. Guidici et al [14] attempted to carry out 1D CNN for classifying land cover from multi-seasonal hyperspectral imagery, followed by the features extracted from the spectral domain through the training of the network. To avoid overfitting, S. Mei et al [15] suggested a spectral-spatial-featurebased classification framework, which jointly makes use of batch normalization, dropout, and parametric rectified linear 2 Mathematical Problems in Engineering unit activation function and a 1D CNN.…”
Section: Introductionmentioning
confidence: 99%